2014
DOI: 10.3329/jbau.v11i1.18196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different doses of GA3 application at primordia initiation stage on the growth and yield of Oyster mushroom

Abstract: Gibberellic acid (GA 3 ) was sprayed with eleven doses viz. 0, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 ppm at the primordia initiation stage to evaluate its effect on the growth and yield performance of Oyster Mushroom. At 10 ppm level GA 3 gave the highest economic yield and dry weight. Application of GA 3 increased the fresh economic yields to about 30% and 34%, while 80% and 115% dry weights increase occurred compared to the control at first and second harvests, respectively. GA 3 showed a positive effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…Overall, there was an increase in total yield with the application of GA3 in different treatments when compared to control. The obtained result was statistically significant and similar to the findings (Dey et al, 2007;Sarker and Chowdhury, 2014;Dey, 1996;Ashrafuzzaman et al, 2005).…”
Section: Yieldsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, there was an increase in total yield with the application of GA3 in different treatments when compared to control. The obtained result was statistically significant and similar to the findings (Dey et al, 2007;Sarker and Chowdhury, 2014;Dey, 1996;Ashrafuzzaman et al, 2005).…”
Section: Yieldsupporting
confidence: 91%
“…The first harvest was nonsignificant (Table 1). Similar results were obtained from (Sarker and Chowdhury, 2014;Dey et al, 2007;Ashrafuz zaman et al, 2005;Xavier et al, 2001).…”
Section: Thickness Of Pileussupporting
confidence: 85%
“…Significantly the highest run rate was recorded at 70% moisture level [12]. pH of the straw before adding chalk and gypsum was 5.8 .This might be because of the acids produced by microbes in substrates during soaking of substrates in water since it was soaked overnight.…”
Section: Substratesmentioning
confidence: 94%
“…Highest yield is observed at pH 7 even though there is no significant yield difference at the pH 6-8 [13,14]. However, the biological efficiency, biological yield and economic yield were increased with the increase of pH levels up to 5.04 and then decreased [12]. On contrary, Nwokoye et al [15] showed that P. ostreatus was able to grow optimally at pH of 9.…”
Section: Substratesmentioning
confidence: 99%
“…Zerihun Tsegaye (2015) found that the number of fruiting bodies recorded is related to their mycelia colonization. Sarker and Chowdhury (2013) reported that the concentration level 10 ppm and 20 ppm produced the highest number of effective fruiting body. This similar finding has also been reported by Day et al, (2007).…”
Section: Number Of Fruitingmentioning
confidence: 99%